Potensi Pengembangan Ekonomi Kreatif dan Tantangan UMKM di Desa Cepokomulyo - Muhammad Nafi’ Maula; Ahmad Muzaki Aziz; Putri Febriana Setianingtyas; Nailla Mariska Alhumaira; Lilif Mualifatul Khorida Filasofa (Jurnal Pelayanan Masyarakat, 2024)
The creative economy is a concept for realizing sustainable economic development based on creativity. Improving the welfare and prosperity of society in a country is very dependent on the level of economic development. Developing a village economy means making the village economy independent. Cepokomulyo Village is a village with an area that is mostly agricultural land and local crafts that have the potential to be marketed more widely. This makes it easier for people to explore economic potential through abundant fertile land to fulfill their daily activities. However, this potential has not been fully developed optimally due to limited infrastructure, human resources and market access. With this, KKN UIN Walisongo Semarang students play a role in empowering MSMEs to increase and disseminate the economic potential that exists in Cepokomulyo Village by carrying out several activities including holding educational seminars related to digitalization by inviting speakers who are experts in their fields to increase community insight into the economic and digital fields. marketing, providing skills training through processing village agricultural products, as well as helping to build marketing networks. This research uses qualitative research methods through primary and secondary data collection. Meanwhile, the subjects of this research are MSMEs in Cepokomulyo Village. It is hoped that the MSME development empowerment program will have an impact on effective and productive sales, higher quality, and products that can be recognized by all groups in order to compete at national and international levels, provide motivation to the community, and reach wider marketing reach.